Pengaruh Games With Rules Terhadap Pendidikan Karakter Disiplin Pada Anak - Sari, Mita; Ningsih, Sulastya; Djamin, Nunung Suryana; Aini, Nurul; M. Sumirat, Elva (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2024)
This research is motivated by the lack of discipline among the Group B children at Ki Hajar Dewantoro Kindergarten in Gorontalo City. The purpose of this research is to determine the effect of games with rules on the character education of discipline in group B children at Kihajar Dewantoro Kindergarten in Gorontalo City. The method used in this research is quantitative experimentation. The sample in this study consists of 10 children aged 5-6 years. Data collection was carried out through observation of children using the method of games with rules. The research findings indicate that games with rules has an impact on the character education of discipline in group B children at Kihajar Dewantoro Kindergarten in Gorontalo City. The results of the research indicate that games with rules has an impact on the character education of children's discipline, as games with rules can encourage children to develop attitudes, mentalities, and change their behavior towards a more positive direction. In this study, children can recognize and develop their self discipline through enjoyable games. The research results can be considered significant because games with rules has advantages in developing character education and discipline in early childhood.